Rehabilitasi Eks-Pecandu Narkoba Melalui Pendekatan Agama Islam - Ahmad Saefulloh (Islamic Counseling : Jurnal Bimbingan dan Konseling Islam, 2018)
This effort can not be fully burdened to the government only, there needs to be synergy between government, society, parents, and related institutions in their field. This effort is one form of mutual concern that has been listed in the Narcotics Act, and the cultivation of values of Islamic Religious Education as a preventive effort that is being done. The existence of rehabilitation efforts through the Islamic approach is one alternative to prevent the return of ex-drug addicts in harmful environments. The purpose of this research is to explain how the rehabilitation of drug addicts through Islamic approach. The research method used qualitative method, then the research data was collected through interview and document analysis, and then processed by using qualitative descriptive analysis. The results show that there are three approaches of Islam by planting Religious education values that can be applied such as: (1) The Cultivation of the Aqidah Educational Values; (2) Planting the values of religious education; (3) The cultivation of moral values.